Revisiting the taxonomy of Geranium rubifolium (Geraniaceae) with notes on its habitat and conservation status - Wagh, Vijay V.; Hurrah, Imtiyaz Ahmad (Phytotaxa, 2020)
Geranium rubifolium (Geraniaceae) has been rediscovered while conducting floristic sampling for the monographic studies on the genus Geranium from Indian Himalayan region. The species was described 179 years ago by John Lindley by using Iconotype, serving as the type and the only known material of the taxon. The locality of Lindley’s collection (collection made by Dr. Royle) is imprecisely described, as he only mentioned ‘the Himalaya’ where the taxon is found. Therefore any search attempt would require an extensive exploration of the Indian Himalayan region. Morphological variation of G. rubifolium has been poorly understood because of the non-availability of representative specimen. Consequently, after rediscovering the taxon, we provide here the detailed taxonomic description, notes on habitat, distribution and its conservation status.